Preferensi konsumen dalam berbelanja pada online shop - Arbi Musa; Erida Erida; Ade Titi Nifita (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to analyze consumer preferences in shopping at online shops. The dimensions of the product attribute in this study are Merchandise (always ready goods, various products, items according to photos), customer service (fast delivery of goods, responsive AI chatbot, easy credit process), navigation (good layout, search through filters, easy login), Security (COD system, safe delivery of goods (warranty), safe user data). The analysis tool used is the average analysis methodandconjoinedanalysis with the SPSS version 21 application. The results showed consumer preferences in shopping at the online shop. These products vary in the dimensions of Merchandise, fast processing of goods on the dimensions of customer service and promotion, good layout on the navigation and convenience dimension, and the cash on the delivery system on the security dimension. This research is expected to guide online shop developers to develop applications, web systems, and digital services that refer to the sizes that consumers prefer.